Perbedaan Model Problem Based Learning dan Discovery Learning Terhadap Hasil Belajar Tematik Terpadu - Sagita, Rahma; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This purpose of this research is to know the difference of the use of problem based learning model and discovery learnig model the learning outcomes of thematic learning of grade V of Cluster II, Ampek Angkek sub-district, Agam district.The type of research used is experimental research. In this study using a Quasi experimental design research design with the form of pretest-posttes non-equivalent group design. The sample technique used is simple random sampling with the research sample is SDN 15 Ampang Gadang consisting of VA and VB classes. The results of the study using the T test can be known tcount 2.73> ttable 1.72 at α 0.05 level. Thus it can be concluded that there is a significant difference between the use of the Problem Based Learning model and the Discovery Learning model towards integrated thematic learning outcomes in class V of cluster II, Ampek Angkek District, Agam Regency.